2021
DOI: 10.1021/acsomega.1c03696
|View full text |Cite
|
Sign up to set email alerts
|

Methane–Air Plasma-Assisted Ignition Excited by Nanosecond Repetitively Pulsed Discharge: Numerical Modeling and Effect of Inert Gas

Abstract: Plasma-assisted ignition and combustion are promising approaches for controlling ignition enhancement and flame stabilization. The global loosely coupled plasma-assisted combustion kinetic model has been established by combining the ZDPlasKin and ChemKin codes, which is employed to numerically investigate the effects of the inert gas-diluted methane−air nanosecond repetitively pulsed (NRP) plasma on the ignition process. The results indicate that addition of the inert gas is conducive to increasing the chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Additionally, reports have shown that adding an inert gas such as Ar increases the electron energy and enhances the electric field . This increases electron impact reaction with gas phase molecules and promotes plasma-phase chemistry. There is also the potential to create metastable species, which undergo Penning ionization through impact collision and energy exchange with neutral species such as NH 3 . , …”
Section: Plasma Catalysis For Hydrogen Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, reports have shown that adding an inert gas such as Ar increases the electron energy and enhances the electric field . This increases electron impact reaction with gas phase molecules and promotes plasma-phase chemistry. There is also the potential to create metastable species, which undergo Penning ionization through impact collision and energy exchange with neutral species such as NH 3 . , …”
Section: Plasma Catalysis For Hydrogen Generationmentioning
confidence: 99%
“… 296 This increases electron impact reaction with gas phase molecules and promotes plasma-phase chemistry. 296 298 There is also the potential to create metastable species, which undergo Penning ionization through impact collision and energy exchange with neutral species such as NH 3 . 196 , 299 …”
Section: Plasma Catalysis For Hydrogen Generationmentioning
confidence: 99%
“…In order to overcome the problems in the lean combustion process, plasma-assisted combustion technology has been widely studied. With the progress of plasma-assisted ignition and combustion, plasma-assisted combustion technology is expected to become a more effective combustion control method . Plasma assists combustion mainly through three pathways: (1) thermal effect; (2) activation effect; (3) transport effect.…”
Section: Introductionmentioning
confidence: 99%